Telecommunications and the World Trade Organization : the case of Mexico - Wellenius, Björn (Policy research working paper, 2005)
"The U.S.-Mexico case (2002-04) was the first (and so far only) case of World Trade Organization (WTO) dispute resolution on telecommunications services and the first on services only. The findings of the Panel charged with settling the dispute contain interpretations of the General Agreement on Trade in Services (GATS), especially its Annex on Telecommunications and the Reference Paper that sets regulatory principles. Although these interpretations strictly apply only to the case examined, they have implications for other countries and sectors and beyond trade law. The following are some of the findings. Telecommunications services originated in one country and terminated in another country are cross-border services under the GATS irrespective of whether the same service provider is present in both countries. The accounting rate regime, whereby operators share revenue from international services provided jointly, is subject to the discipline of cost-based interconnection for countries that have adopted the Reference Paper. Uniform settlement rates and proportional return are anticompetitive practices under the Reference Paper even when they are mandated by law. The lack of implementing regulations does not excuse the country from meeting its commitments under the GATS. Mexico and the United States, although not in full agreement with the Panel, did not appeal. An agreed plan to address the underlying legal and regulatory issues was successfully implemented in July 2005. "--World Bank web site